2016
DOI: 10.1002/anie.201601976
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Cyclobutylboronates via a Copper‐Catalyzed Desymmetrization Approach

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: In this report, the first catalytic enantioselective synthesis of cyclobutylboronates, using a chiral copper(I) complex, is disclosed. A broad variety of cyclobutanes have been prepared with consistently high levels of diastereo-and enantiocontrol. Moreover, this method constitutes the first report of an enantioselective desymmetrization of meso-cyclobutenes to prepare chiral cyclobutanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 72 publications
0
44
0
2
Order By: Relevance
“…[7] Reports of catalytic enantioselective methods are equally rare.Acoppercatalyzed enantioselective formal hydroboration of symmetrical 2,3-disubstituted cyclobutenes was reported by Tortosa and co-workers ( Figure 2a). [8] Because of its distinctive feature as ad esymmetrization, this method is limited to symmetrically disubstituted cyclobutenes.R ecently,Y ua nd co-workers described adirected catalytic enantioselective CH borylation of cyclobutyl carboxamides that provides cyclobutylboronates in high enantioselectivity with ad istinct substitution pattern ( Figure 2b). [9,10] To develop ag eneral, complementary approach to access cyclobutylboronates,w e envisioned using ac opper-catalyzed conjugate borylation of cyclobutenones.P ioneering work by Hosomi [11] has shown that conjugate borylation provides an extremely efficient entry into optically enriched cyclopentyl-and cyclohexylboronates, [12,13] however the cyclobutane equivalent is lacking in the literature.T oaddress this void, we targeted the conjugate borylation of a,b-disubstituted cyclobutenones (Figure 2c), which would provide the first examples of enantioenriched tertiary cyclobutylboronates.…”
mentioning
confidence: 99%
“…[7] Reports of catalytic enantioselective methods are equally rare.Acoppercatalyzed enantioselective formal hydroboration of symmetrical 2,3-disubstituted cyclobutenes was reported by Tortosa and co-workers ( Figure 2a). [8] Because of its distinctive feature as ad esymmetrization, this method is limited to symmetrically disubstituted cyclobutenes.R ecently,Y ua nd co-workers described adirected catalytic enantioselective CH borylation of cyclobutyl carboxamides that provides cyclobutylboronates in high enantioselectivity with ad istinct substitution pattern ( Figure 2b). [9,10] To develop ag eneral, complementary approach to access cyclobutylboronates,w e envisioned using ac opper-catalyzed conjugate borylation of cyclobutenones.P ioneering work by Hosomi [11] has shown that conjugate borylation provides an extremely efficient entry into optically enriched cyclopentyl-and cyclohexylboronates, [12,13] however the cyclobutane equivalent is lacking in the literature.T oaddress this void, we targeted the conjugate borylation of a,b-disubstituted cyclobutenones (Figure 2c), which would provide the first examples of enantioenriched tertiary cyclobutylboronates.…”
mentioning
confidence: 99%
“…Further elaboration of the C−B bond is possible. For example, the oxidation of 5 and 5′a under standard conditions yielded N‐protected, cyclobutyl‐β‐amino alcohols 6 and 6′a (Scheme ) . Boronic esters 5 and 5′a can also be readily converted into potassium trifluoroborate salts 7 and 7′a using the KF/tartaric acid procedure developed by Lennox and Lloyd‐Jones (Scheme ) …”
Section: Methodsmentioning
confidence: 91%
“…Mehrere Arbeitsgruppen berichteten zudem über das Abfangen des bei der Kupfer-katalysierten 1,4-Borylierung entstehenden Kupferenolats mit Aldehyden und Ketonen in sowohl inter-a ls auch intramolekularen Prozessen gemäßeiner Aldolreaktion. [59,60] Im Rahmen interessanter Weiterentwicklungen von Kupfer-katalysierten asymmetrischen Protoborierungsreaktionen berichteten Ito und Mitarbeiter vor kurzem über mehrere Untersuchungen zur Kupfer-katalysierten enantioselektiven borylierenden Funktionalisierung von Heterocyclen. Hoveyda und Mitarbeiter berichteten 2009 über die enantioselektive Kupfer-katalysierte Protoborierung von arylsubstituierten Alkenen (ohne weitere Aktivierung durch eine konjugierte Carbonylfunktion).…”
Section: Angewandte Chemieunclassified
“…Tortosa und Mitarbeiter berichteten außerdem über die asymmetrische Protoborierung von Cyclopropenen und Cyclobutenen mit B 2 pin 2 unter Kupfer/Bisphosphan-Katalyse. [59,60] Im Rahmen interessanter Weiterentwicklungen von Kupfer-katalysierten asymmetrischen Protoborierungsreaktionen berichteten Ito und Mitarbeiter vor kurzem über mehrere Untersuchungen zur Kupfer-katalysierten enantioselektiven borylierenden Funktionalisierung von Heterocyclen. Mit elektronenarmen Indolen gelang Ito und Mitarbei-tern die Durchführung einer enantioselektiven borylierenden Dearomatisierung mit B 2 pin 2 ,b ei der mit hervorragender asymmetrischer Induktion chirale 3-Borylindoline entstanden (Schema 17).…”
Section: Angewandte Chemieunclassified